Efficacy of nearuv-a to inactive microbial growth. (20th October 2021) - Messina, G; Manetti, C; Amodeo, D; De Palma, I; Petri, C; Nante, N; Cevenini, G
Abstract: Background: Microbes are less able to develop resistance towards antimicrobial blue light (aBL), at 405nm, towards disinfectants/antibiotics. In addition, Near UV-A light (nUV) is less harmful to host cell compared to UV-C irradiation. This study aimed to assess the efficiency aBL in reducing microbial growth on surfaces. Methods: This cross-sectional study, run between July-October 2020. Petri dishes were contaminated with P. Aeruginosa, E. Coli, S. Aureus, S. Typhimurium, K. Pneumoniae at a concentration of 1.5x104 CFU/mL and were placed at 2 and 3m of distances from the light source having an irradiance of 967, 39 and 497, 33 µW/cm2 for 12 hours. The air confined the room was sampled for two weeks with two air samplers (SAS), before and after the exposition to the nUV light source to estimate the reduction of the environmental microbial contamination. The analysis was conducted using Stata software. Final results were expressed as logarithmic reduction mean with 95% confidence interval. Results: The highest microbial reduction was reached 2m directly under the light. Significant (p < 0.05) log-reduction were achieved for S. Typhimurium, 2.93 (IC 2.44-3.40), K.Pneumoniae, 2.30 (IC 2.14-2.46), S.Aureus, 3.98 (IC 3.78-4.12), E.Coli, 3.83 (IC 3.17-4.50), P. Aeruginosa, 3.86 (IC 3.22-4.48). At 3m of distance from the light source, it was observed a significant logarithmic reduction for S. Aureus, 3.49 (IC 3.34-3.65), and P. Aeruginosa, 3.80 (IC 3.11-4.47). In the air tests, we observed a mean percentage microbial reduction of about 70% after 12 h of exposure to nUV light. Conclusions: nUV has proven to contrast microbial growth on the plates. It is possible to implement this technology in the environment for controlling microbial presence in "ad hoc" scenario but also in common areas. Mitigating the energy, it is possible to use this technology in presence of persons. Key messages: In this experimental study, nearUV-A has proven to be efficient to reduce the microbial growth and to disinfect air and surface. NearUV light (nUV) can be use as an innovative technology for decreasing bacterial contamination, also in presence of people.